DESAIN RUMAH TINGGAL TROPIS DI SEMARANG - Yohana Nursruwening; Wita Widyandini (Fakultas Teknik, Universitas Wijayakusuma Purwokerto, 2020)
Indonesia has a humid tropical climate with the characteristics of uniform solar radiation throughout theyear, low air pressure, always cloudy air, high air temperatures and very high humidity. With thecharacteristics of the tropical climate, there are many problems in anticipating climate, therefore specialhandling is needed in designing buildings, one of which is a dwelling to achieve comfortable conditionsfor its inhabitants. How to create a residential design that is friendly to the climate for the humid tropics ?.This design is expected to provide an illustration for the designer and all levels of society the importantrole of building houses that are friendly to the tropical climate. The design method is carried out so thatthe building is friendly to the tropical climate through building orientation, cross ventilation, control ofsolar radiation, temperature, humidity and vegetation.Based on the analysis, it was concluded that in the Design House area in Semarang with an average DryTemperature of 30.7 ° C and an Relative Humidity of an average of 74% to achieve Thermal comfort airmovement with a wind speed of 3.5 m / sec is needed, has a Humid Temperature of 26.9 ° C, the EffectiveTemperature of 25.0 ° C.Keywords : Design, Residential, Tropical Climate, Air Humidity, TemperatureABSTRAKIndonesia mempunyai iklim tropis lembab dengan ciri-ciri penyinaran matahari merata ssepanjang tahun,tekanan udara rendah, udara selalu berawan, temperatur udara yang cukup tinggi dan kelembaban udarayang sangat tinggi. Adanya ciri-ciri iklim tropis tersebut maka banyak persoalan mengantisipasi iklim,oleh karena itu perlu penangan khusus dalam merancang bangunan salah satunya Rumah Tinggal untukmencapai kondisi nyaman bagi penghuninya Bagaimana menciptakan suatu desain Bangunan RumahTinggal yang bersahabat dengan iklim untuk daerah tropis lembab?.Desain ini diharapkan dapat memberikan gambaran bagi perancang dan semua lapisan masyarakatpentingnya peranan bangunan rumah tinggal yang bersahabat dengan iklim tropis. Metode perancanganyang dilakukan agar bangunan tersebut bersahabat dengan iklim tropis yaitu melalui orientasi bangunan,ventilasi silang, kontrol terhadap radiasi matahari, temperatur, kelembaban udara dan tumbuhan.Berdasarkan analisa yang dilakukan diperoleh kesimpulan bahwa pada kawasan Rumah Rancangan diSemarang dengan Temperatur Kering rata-rata 30,7°C dan Kelembaban Relatif rata-rata 74% untukmencapai kenyamanan Thermal dibutuhkan gerakan udara dengan kecepatan angin sebesar 3,5 m/det,memiliki Temperatur Lembab sebesar 26,9 °C, Temperatur Efektifnya adalah 25,0 °C.Kata Kunci : Desain, Rumah Tinggal, Iklim Tropis, Kelembaban Udara, Temperatur